2022
DOI: 10.7759/cureus.23417
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Tuberculosis in the Setting of COVID-19 Infection

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) was declared a pandemic by WHO in March 2020. The causative organism has since undergone a series of mutations. COVID-19 primarily being a respiratory illness causes pre-existing pulmonary diseases to show worse clinical outcomes. About one-third of the world’s population is thought to be infected with latent Mycobacterium tuberculosis (MTB). Both previous and newly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…This is through a process that activates a specific gene stemness, ultimately leading to MTB reproduction and reactivation. However, this phenomenon is yet to be confirmed, as it’s been observed in mice [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is through a process that activates a specific gene stemness, ultimately leading to MTB reproduction and reactivation. However, this phenomenon is yet to be confirmed, as it’s been observed in mice [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…Coronavirus disease 2019 (COVID- 19), the ongoing pandemic that originated in China in December 2019, is a significant public health threat. More than 100 million cases and 2.3 million deaths worldwide have been reported to the world health organization (WHO) [1].…”
Section: Introductionmentioning
confidence: 99%
“…17 There is evidence that, for patients with COVID-19 disease, there is an increased risk of latent tuberculous infection progressing to active tuberculosis (TB). 18 COVID-19 disease is also associated with reactivation of latent cytomegalovirus infection. 19 A striking example of the impact of SARS-CoV-2 on the emergence of secondary fungal infection is the association with severe mucormycosis that was observed in India, during the height of the COVID pandemic.…”
Section: Discussion Of Case and Relevant Literaturementioning
confidence: 99%
“…The patient was a known case of chronic obstructive pulmonary disease, coronary artery disease, seizure disorder and heart failure with reduced ejection fraction. 18 Landivar et al reported a case of 69-year-old female who developed pulmonary tuberculosis few months after severe COVID-19 infection for which she received dexamethasone and tocilizumab. The patient was a known case of hypertension, diabetes, pancreatitis (autoimmune type 1).…”
Section: Methodsmentioning
confidence: 99%